Resveratrol exhibits neuroprotection against paraquat-induced PC12 cells via heme oxygenase 1 upregulation by decreasing MiR-136-5p expression. Issue 3 (1st March 2022) - Zhang, Li; Dong, Min-Na; Deng, Jun; Zhang, Chun-Hai; Liu, Ming-Wei
ABSTRACT: Resveratrol (Res) is a flavonoid with an antioxidant effect and has been utilized to treat oxidative stress-related illnesses; however, its mechanism remains ambiguous. This research aims to explore whether Res inhibits miR-136-5p expression, increases heme oxygenase 1 (HMOX1) expression, and mitigates oxidative stress and PC12 cell apoptosis triggered by paraquat (PQ). Results showed that PQ dose-dependently increased the expression of miR-136-5p, the apoptosis of PC12 cells, the activities of reactive oxygen species (ROS), and the levels of lactate dehydrogenase (LDH), malondialdehyde (MDA), caspase-3, and pro-apoptotic protein Bax. In addition, PQ reduced the expression of anti-apoptotic protein Bcl-2, HMOX1 mRNA and protein, and nuclear factor-erythroid factor 2-related factor 2 (Nrf2) protein and the activity of superoxide dismutase 1 (SOD1) and PC12 cells. After the PQ-treated PC12 cells were administered with different Res concentrations for 24 h, the miR-136-5p expression was dose-dependently decreased. An increase was observed in the activity and survival rate of PC12 cells, the protein and mRNA levels of HMOX1 and Nrf2, and the content of anti-apoptotic protein B-cell lymphoma/leukemia gene-2 (Bcl-2). By contrast, the activities of ROS, LDH, and MDA and the apoptosis of PC12 cells decreased. These findings illustrated that Res could reduce the oxidative stress and apoptosis triggered by PQ and enhance the activity and survival rate of PC12 cells. The underlying mechanism might be correlated with the reduced miR-136-5p expression and the elevated activity of the HMOX1/Nrf2 pathway. Graphical abstract: uf0001